Quality of drinking water from the agricultural area treated with pitcher water filters - Elżbieta Królak; Jolanta Raczuk; Danuta Sakowicz; Elżbieta Biardzka (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Home methods of drinking water treatment through filtration have recently become quite popular. Objective. The aim of the study was to compare chemical composition of unfiltered water with water filtered in households with pitcher water filters. Obtained results were discussed in view of the effect of analysed chemical components of water on human health. Material and methods. Water samples were taken from water works supplies and from home dug wells from the agricultural area. Unfiltered water and water filtered through filters filled with active carbon and ion-exchanging resin and placed in a pitcher were analysed. Electrolytic conductivity, pH, hardness and the concentrations of calcium, magnesium, nitrate, phosphate and chloride ions were determined in water samples. Results of analyses were statistically processed. Results. As a result of water filtration, the concentration of phosphates significantly increased and the concentrations of calcium, magnesium, electrolytic conductivity and pH decreased. No changes were noted in the concentration of chloride ions. Filtering water decreased the concentration of nitrates in dug wells samples. Conclusions. Using water purification devices is justified in the case of water originating from home dug wells contaminated with nitrates when, at the same time, consumers' diet is supplemented with calcium and magnesium. Filtration of water from water works supplies, controlled by sanitary inspection seems aimless.